Teachers` perception of the standard-based English language curriculum in Malaysian primary schools - Sulaiman, Suriati; Sulaiman, Tajularipin; Rahim, Suzieleez Syrene Abdul (International Journal of Instruction, 2017)
Standard-based English language curriculum (SBELC) was fairly a new curriculum in Malaysian primary schools. The implementation of SBELC is a phenomenon affecting all teachers and pupils in primary education. Since curriculum implementation occurs mostly in the classroom and teachers are the key players in the implementation process, the initial concern should be teachers’ perceptions towards the new language curriculum. Teachers’ perceptions towards the curriculum determine their acceptance and readiness. Therefore, a multiplecase study was carried out that involved five teachers from five national primary schools to investigate teachers’ perceptions towards the implementation of the SBELC and data were analysed from classroom observations, semi-structured interviews, and corresponding documents. The findings suggested the participants had positive perceptions towards the new language curriculum which were the early indicator of their acceptance and readiness to implement the standard-based English language curriculum. This paper attempts to discuss teachers’ perceptions of the standard-based English language curriculum as progressive, pragmatic and outcome-based curriculum in Malaysian primary schools.